Działalność gospodarcza ks. Franciszka Józefa Wybickiego (1709-1765) - Kropidłowski, Zdzisław (Archiwa, Biblioteki i Muzea Kościelne, 2009)
Priest Franciszek Józef Wybicki came from a moderately rich noble family, who rendered great service to the country. Judging from the numerous posts he served at the request of the bishops of Włocławek, he was an educated theologian and lawyer. Apart from managing the parish of the Archangel Michael in Skarszewy (1736-1765), he was a surrogate to several general officials in Gdańsk since 1743; in 1747 he was first mentioned as one of the canons in the Włocławek chapter. Since 1758 he was the chancellor of the Kruszwice chapter and the archdeacon of the Pomorian District since 1764. His business activity was limited to the parish in Skarszewy, situated in the vicinity of Gdansk. First of all, he rebuilt the parish church, which had been consecrated in 1750, where he founded two altars: the main altar, devoted to the Archangel Michael and the one devoted to St Mary. In addition, he built a poor-house for 8 people and furnished it generously. The farm buildings were also restored. He tried to regain the sums due to the provosts of Skarszewy, suing the debtors in six trials; he won one case, two others were still in court when he died and, in view of the fact that he lacked sufficient evidence to win, he renounced the remaining ones. Priest F.J. Wybicki did not do any business himself; he was content with rebuilding and leasing two home farms, a large and a small one; he also regenerated the parish forest and renounced the taproom rights. He collected tithes, offerings on account of iura stolae or Christmas visits, Easter confessions or donations for celebrating masses. The total parish revenues came up to 3 thousand florins and about 200 bushels of wheat and oats. The tenants were obliged to work 132 days a year for him. Owing to his efforts, the revenues rose by 50%, the parish remaining one of the most profitable in 18th century Poland. It should be noted that he resigned the offerings of the guild of bakers, whose request to do so was based on their difficult financial situation.